From old socialists to new democrats - Hyde, S; Hyde, Sarah Jane (2005)
﻿ In 1996, a new left of centre party emerged in Japan called the Democratic Party of Japan (DPJ) and effectively replaced the Japan Socialist Party (JSP) as the main opposition party. This thesis asks what conditions caused this realignment and how the DPJ differs from the JSP. An increasing distrust and disinterest of politics and politicians has meant that the non-aligned voter in Japan forms the largest group of the electorate. Every party has lost support, but the left faced the worst drop of support. With the end of the Cold War, and the intensifying call for Japan to reassess its role on the World stage, the traditional ideology of the Japanese left, which has become synonymous with peace and preservation of the Peace Constitution, has lost its stabilising effect on the party and on its supporters. The labour unions, which were once the key mobilisational force for the left-wing parties at election time, began to question their relationship with the JSP and found new links to government. Simultaneously, they were also losing members so mobilisation of voters for the left also declined. Finally, a new electoral system did not reward the opposition as much as the LDP. Overall, the mobilisation of the electorate has become increasingly difficult for the Japanese left as a result of these factors. The DPJ has had to find ways of dealing with them and also has had to create its own identity. The way in which the party has dealt with this is by 'widening out' its types of candidate and using new methods to attract support. Furthermore, the DPJ has become more aware of its party coherence and has ensured that party unity is maintained even when ideological disputes occur.